2004
DOI: 10.1292/jvms.66.1205
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polysaccharides and Carboxymethylcellulose Combination to Prevent Intraperitoneal Adhesion and Abscess Formation in a Rat Peritonitis Model

Abstract: ABSTRACT. Polysaccharides isolated from fungi, Phellinus spp. is well-known material with anti-tumor and anti-inflammatory properties. We have assessed the adhesion-and abscess-reducing capacity of carboxymethylcellulose (CMC) and polysaccharides from Phellinus spp. combination in a rat peritonitis model. In 72 Sprague-Dawley rats, experimental peritonitis was induced by means of the ce cal ligation and puncture model (CLP). After 24 hr, the abdomen was reopened and the ligated cecum was resected. Peritoneal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…Among these Phellinus mushrooms, PG used in this study has advantages over the other Phellinus mushrooms in that it has a very short growth period (3 months) compared to other Phellinus mushrooms (2-3 years) making it cheaper to produce. In addition, our recent studies have demonstrated significant anti-inflammatory properties of PG such as inhibition of pulmonary inflammation [11] and prevention of intraperitoneal adhesion under infection [1,3,6]. We therefore predict that medicinal application of PG has many advantages in medical cost-cutting as well as benefits in clinical application in future.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Among these Phellinus mushrooms, PG used in this study has advantages over the other Phellinus mushrooms in that it has a very short growth period (3 months) compared to other Phellinus mushrooms (2-3 years) making it cheaper to produce. In addition, our recent studies have demonstrated significant anti-inflammatory properties of PG such as inhibition of pulmonary inflammation [11] and prevention of intraperitoneal adhesion under infection [1,3,6]. We therefore predict that medicinal application of PG has many advantages in medical cost-cutting as well as benefits in clinical application in future.…”
mentioning
confidence: 96%
“…We have previously demonstrated that polysaccharides isolated from PG inhibit pulmonary inflammation [11] and intraperitoneal adhesion related to intraperitoneal inflammation [1,3,6]. These effects of PG related to anti-inflammatory activities might be beneficial in the treatment of dermal wound healing.…”
mentioning
confidence: 98%
“…Our previous studies showed that PG inhibits the increase of inflammatory cells and IL-1β concentration in bronchial lavage fluid in lipopolysaccharide-challenged rats and might be useful in preventing acute pulmonary inflammation in human diseases. 12) It was also reported that PG has significant adhesion-and abscess-reducing effects in a rat peritonitis model, 13,14) and has significant dermal wound healing effects clinically. 15) The results of the previous and present studies provide clear evidence for the antiinflammatory effect of PG in acute and chronic inflammatory diseases.…”
Section: Resultsmentioning
confidence: 96%
“…12) Therefore, it is conceivable that aqueous extracts of PG may have the anti-inflammatory effects. PG has also significant adhesion-and abscess-reducing effects in a rat peritonitis model, 13,14) and has significant dermal wound healing effects clinically. 15) Vol.…”
Section: Introductionmentioning
confidence: 99%
“…While mannitol is considered an inert substance, recent research has suggested possible interdependencies with monocyte and neutrophil function (upregulation of HLA-DR in monocytes, upregulation of CD11b in neutrophils and monocytes, and inhibition of neutrophil apoptosis (Turina et al, 2008)). Hydroxyethyl starch (Handrigan et al, 2005;Matharu et al, 2008) and cellulose (Hänsch et al, 1996;Moore et al, 2001;Bae et al, 2004;Ewoldt et al, 2004;Hernández et al, 2004Hernández et al, , 2009 have also both been shown to alter inflammatory responses due to their different effects on neutrophils. While glucose is also able to support the maintenance of oncotic pressure (Hicks et al, 2006), it supports the specimen's metabolism and survival.…”
Section: Cell Free Solutionsmentioning
confidence: 99%